Tanna times : islanders in the world - Lindstrom, Lamont, 1953- (Honolulu : University of Hawaiʻi Press, 2021)
This book introduces the vibrant living culture and fascinating history of Tanna, an island in Vanuatu, Melanesia, through the stories of a dozen interconnected Tanna Islanders.
chapter 1. Ipare -- chapter 2. Sharks -- chapter 3. Mwatiktiki -- chapter 4. Elau -- chapter 5. Mary -- chapter 6. Soarum -- chapter 7. Manehevi -- chapter 8. Nouar -- chapter 9. Sivur -- chapter 10. Kusi -- chapter 11. Kwatia -- chapter 12. Tio and Natis -- chapter 13. Reuben -- chapter 14. Last island.
"This book published as part of the Sustainable History Monograph Pilot" -- Preliminary page.
Includes bibliographical references and index.
Keywords: Tanna Island (Vanuatu) -- History; Tanna Island (Vanuatu) -- Biography